Small molecule perturbation of the CAND1-Cullin1-ubiquitin cycle stabilizes p53 and triggers Epstein-Barr virus reactivation. - Nadezhda Tikhmyanova; Steve Tutton; Kayla A Martin; Fang Lu; Andrew V Kossenkov; Nicholas Paparoidamis; Shannon Kenney; Joseph M Salvino; Paul M Lieberman (PLoS Pathogens, 2017)
The chemical probe C60 efficiently triggers Epstein-Barr Virus (EBV) reactivation from latency through an unknown mechanism. Here, we identify the Cullin exchange factor CAND1 as a biochemical target of C60. We also identified CAND1 in an shRNA library screen for EBV lytic reactivation. Gene expression profiling revealed that C60 activates the p53 pathway and protein analysis revealed a strong stabilization and S15 phosphorylation of p53. C60 reduced Cullin1 association with CAND1 and led to a global accumulation of ubiquitylated substrates. C60 also stabilized the EBV immediate early protein ZTA through a Cullin-CAND1-interaction motif in the ZTA transcription activation domain. We propose that C60 perturbs the normal interaction and function of CAND1 with Cullins to promote the stabilization of substrates like ZTA and p53, leading to EBV reactivation from latency. Understanding the mechanism of action of C60 may provide new approaches for treatment of EBV associated tumors, as well as new tools to stabilize p53.